Effect of Different Wheat-Based Diets and Corn Meal Addition on Development Parameters of Ephestia kuehniella (Zeller, 1879) (Lepidoptera: Pyralidae). Issue 3 (20th May 2022) - Parra, L M; Garcia, A G; Alves, G R; Magro, S R; Parra, J R P
Abstract: The expansion of Integrated Pest Management (IPM), including biological control, has had several positive consequences for the agricultural environment and participants in the production chain. To enable successful operation and applications of biological control, production of insects used for rearing natural enemies (parasitoids and predators) must be optimized to reduce time and costs and improve production both qualitatively and quantitatively. The present study evaluated the effect of wheat varieties, the main component of artificial diets for Ephestia kuehniella, on the reproductive performance and biological parameters of this flour moth, which is used for mass production of Trichogramma spp. (Hymenoptera: Trichogrammatidae) and other parasitoids and predators. Four varieties of wheat were compared: BRS 327, BRS Marcante, BRS Parrudo, and KBR, with and without the addition of corn E. kuehniella reared on 97% BRS 327 wheat flour + 3% nutritional yeast had the best biological parameters and substitution of corn for about half of the wheat increased the number of eggs per female.